Solution Combustion Synthesis of ZrO2:Tb3+ Nanophosphors Viable for WLEDs. (2018) - Ponkumar, S.; Janaki, K.; Prakashbabu, D.; Ramalingam, H.B.; Munirathnam, K.; Hari Krishna, R.
Abstract: Tb 3+ doped Zirconium oxide (ZrO2 ) nanopowders were synthesized by solution combustion method using oxalyl di-hydrazide (ODH). The effect of dopant concentration on the crystal structure and photoluminescence properties of the nano phosphors were investigated. Band gap of the samples were obtained from Wood and Tauc plot. Scanning electron microscopy analysis reveals the formation of porous powders with large amount of voids. Room temperature photoluminescence shows visible luminescence of the phosphors under near UV excitation. The colour index of phosphors were calculated using CIE co-ordinates. These phosphors show bright green emission centered at 550 nm. The emission intensity increased with Tb 3+ concentration up-to 5 mol% and decreased thereon. All these samples were emitting green colour having colour coordinates at (0.25, 0.65). The colour purity of the samples reveals that these phosphors are promising candidates as green emitting phosphors in the tricolor GaN based white light emitting diodes.